Design and study of equipment for accepting and drying soya seeds with high moisture content - Volkhonov, Michael; Smirnov, Ivan; Maksimov, Ivan (Eastern-European Journal of Enterprise Technologies, 2019)
The studied designs of existing equipment for post-harvest processing do not ensure careful reception and drying of high-moisture soya seeds which leads to a decrease in quality and yield loss. To solve this problem, a mobile device was developed and manufactured for accepting and drying in one pass of a high-moisture soya piles, that is, a cloth air-slide conveyor. The developed device design with a low specific quantity of metal provides reception, drying and transportation of high-moisture seeds. These advantages have been achieved through the use of additional air supply ducts in the design and woven materials including woven sieves with a coefficient of open space increased to 46 %. Drying of wet materials is the most critical operation in humid climate areas. The use of existing reception departments and devices for drying and ventilating seeds of leguminous crops does not ensure quality and reduction of costs of drying high-moisture seeds in the areas of high humidity. The use of additional ducts for supplying air from the cloth screens in the design of the cloth air-slide conveyor can additionally increase supply of the drying agent to the pile layer by 60 %. The design of the drying chamber ensures high uniformity of drying with deviation of the relative moisture of soya seeds no more than 1.2 % and an increase in their germination capacity by 4.5 %. The use of the developed cloth air-slide conveyor makes it possible to receive high-moisture seeds of loose crops in batches of various weights and dry them at high quality, without injury in one pass at the least energy consumption. Features of the design open up the possibility of its use in areas of high humidity at enterprises with various product outputs.